2023
DOI: 10.1021/acs.inorgchem.3c00092
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Dinitrogen and Oxygen to Nitric Oxide Mediated by Triatomic Yttrium Cations: Reversible N–N Bond Switching

Abstract: The direct coupling of dinitrogen (N 2 ) and oxygen (O 2 ) to produce value-added chemicals such as nitric acid (HNO 3 ) at room temperature is fascinating but quite challenging because of the inertness of N 2 molecules. Herein, an interesting reaction pathway is proposed for a direct conversion of N 2 and O 2 mediated by all-metal Y 3 + cations. This reaction pattern begins with the N�N triple bond cleavage by Y 3 + to generate a dinitride cation Y 2 N 2 + , and the electrons that lead to N 2 activation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…[42,43] The findings of these studies on clusters may provide some molecular-level reaction mechanisms of N 2 activation on practical NRR catalysts. Particularly, clusters containing Y [44][45][46][47] or Co [48] and some metal carbide clusters, such as Y 2 C 4 À and Y 2 C 4 H À , [46] CoTaC 2 À , [48] V 3 C + , [49] V 3 C 4 À , [50] Ta 2 C 4 À , [51] PtC 4-6 À , [52] FeV 2 C 2 À , [53] FeTaC 2 À , [54] V 3-…”
Section: Introductionmentioning
confidence: 99%
“…[42,43] The findings of these studies on clusters may provide some molecular-level reaction mechanisms of N 2 activation on practical NRR catalysts. Particularly, clusters containing Y [44][45][46][47] or Co [48] and some metal carbide clusters, such as Y 2 C 4 À and Y 2 C 4 H À , [46] CoTaC 2 À , [48] V 3 C + , [49] V 3 C 4 À , [50] Ta 2 C 4 À , [51] PtC 4-6 À , [52] FeV 2 C 2 À , [53] FeTaC 2 À , [54] V 3-…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase studies on “isolated” reactants provide an ideal venue for investigating reaction mechanisms and kinetics at a strictly molecular level. 7,23–26 Recently, some encouraging developments in N 2 activation have been reported in the gas phase studies, 27–31 and the ligand effect significantly affects cluster reactivity. Gas-phase clusters usually contain metal atoms coupled with inorganic ligands, such as oxygen, boron, hydrogen, carbon, sulfur, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, we reported that Y 2 BO + and Y 3 + cations can directly form NO molecules from simple N 2 and O 2 at room temperature, which are the only two gas-phase species that can couple N 2 and O 2 . 38,39 To the best of our knowledge, no gas-phase anion has been reported to be able to react with N 2 and O 2 . According to previous literature reports, noble metal-based catalysts exhibit high reactivity for N 2 activation and conversion, 40−42 and there are few reports on quaternary clusters-mediated N 2 reduction.…”
mentioning
confidence: 99%
“…Gas-phase studies provide an ideal venue for experimental and theoretical mechanistic studies of chemical processes at the strictly molecular level. The activation and functionalization of N 2 or O 2 mediated by gas-phase species have been extensively studied. Quite recently, we reported that Y 2 BO + and Y 3 + cations can directly form NO molecules from simple N 2 and O 2 at room temperature, which are the only two gas-phase species that can couple N 2 and O 2 . , To the best of our knowledge, no gas-phase anion has been reported to be able to react with N 2 and O 2 . According to previous literature reports, noble metal-based catalysts exhibit high reactivity for N 2 activation and conversion, and there are few reports on quaternary clusters-mediated N 2 reduction. , In this context, we identified the reactions for N–O coupling from N 2 and O 2 mediated by the heteronuclear metal anion AuNbBO – .…”
mentioning
confidence: 99%
See 1 more Smart Citation